2021
DOI: 10.11130/jei.2021.36.3.462
|View full text |Cite
|
Sign up to set email alerts
|

Stock Market Reactions to the Comprehensive and Progressive Agreement for Trans-Pacific Partnership’s Approval: Evidence from Vietnam

Abstract: We examine the stock market performance of Vietnam’s listed firms in response to the country’s approval of the Comprehensive and Progressive Agreement for Trans-Pacific Partnership (CPTPP). Employing an event study methodology, we first calculate the abnormal returns of all listed Vietnamese firms around the CPTPP’s approval date. Then, we attempt to link these abnormal returns to firms’ characteristics. We find evidence that the announcement of the CPTPP’s approval is associated with positive abnormal returns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…If a company has an abnormal return, then this indicates that investors respond positively to the company's activities. There are several studies that used CAR as a measurement for investor responses [2]; [25]; [28]; [29]; [56]. Study from Ball and Brown [7] found that there is a significant relationship between announcement date and stock price changes.…”
Section: Investor Responsesmentioning
confidence: 99%
“…If a company has an abnormal return, then this indicates that investors respond positively to the company's activities. There are several studies that used CAR as a measurement for investor responses [2]; [25]; [28]; [29]; [56]. Study from Ball and Brown [7] found that there is a significant relationship between announcement date and stock price changes.…”
Section: Investor Responsesmentioning
confidence: 99%